SOUNDS ELISION BY TAIWANESE UNIVERSITY STUDENTS IN PRONOUNCING ENGLISH PHRASES - Ihsan Tanama Sitio; Rahmadsyah Rangkuti (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2021)
The study aims to figure out the phonological variations of sounds elision realized by Taiwanese university students in pronouncing several English phrases. Eight native Taiwanese students were chosen to support the analysis of the study. They consisted of 8 males and 8 females from the college of humanities and literature of Chung Chen University and from the faculty of foreign languages of Asia University, Taiwan. The study used a descriptive qualitative design. According to Ary, Jacob and Sorensen (2010), qualitative researchers seek to understand a phenomenon by focusing on the total picture rather than breaking it down into variables. The goal is a holistic picture and depth of understanding rather than a numeric analysis of data. After analyzing the data, it was found that the pronunciation of the elision of initial /h/, final /t/ and final /d/ sound realized by the Taiwanese university students were varied. Some still pronounced them and some elided them.